The Influence of the Jigsaw Method, Classroom Activeness, and Level of Understanding on Learning Outcomes in Robotic System Practices at SMKN 8 Tangerang City - Asih Awalia; Bagus Dwi Cahyono; Irwanto (The Future of Education Journal, 2025)
This research examines the impact of the Jigsaw teaching approach, class activeness and level of understanding on student learning outcomes in the practice of robotic systems at SMKN 8 Tangerang City. Utilizing a quasi-experimental framework alongside a quantitative method, the research included two groups: one experimental and the other control. The analysis of data was carried out using SPSS version 25 and Microsoft Excel. The results showed that class engagement and level of understanding had a significant influence on student learning outcomes. Simple regression tests showed that class engagement contributed 81% (R² = 0.810) and comprehension level 78.7% (R² = 0.787) to learning outcomes. The multiple regression test showed the combination of these two variables contributed 85.6% (R² = 0.856). The Wilcoxon test showed the Jigsaw method effectively improved learning outcomes with a significance value of 0, without a decrease in scores on the posttest and the majority of students experienced an increase with an average positive rating of 32.00.